2022
DOI: 10.2147/hiv.s354716
|View full text |Cite|
|
Sign up to set email alerts
|

Virological and Immunological Antiretroviral Treatment Failure and Predictors Among HIV Positive Adult and Adolescent Clients in Southeast Ethiopia

Abstract: Background Antiretroviral therapy (ART) regimen failure is linked to an increased risk of disease progression and death, while early detection of ART failure can help to prevent the development of resistance. This study aimed to evaluate virological and immunological ART failure and predictors among HIV-positive adult and adolescent clients in southeast Ethiopia. Methods A retrospective cohort study was implemented from January 2016 to November 30, 2020; all HIV-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Findings in this study identified the number of doses missed as a key predictor of virological failure in patients who missed two or more doses within a month. This result is in accordance with the literature in North Eastern Ethiopia [12] and South Eastern Ethiopia [36], where patients who missed their appointments were likely to miss their doses and increase the odds of virological failure. Other studies from Myanmar [37] and Australia [38] also agreed with this finding, that missed appointments caused missed doses among patients on ART.…”
Section: Discussionsupporting
confidence: 91%
“…Findings in this study identified the number of doses missed as a key predictor of virological failure in patients who missed two or more doses within a month. This result is in accordance with the literature in North Eastern Ethiopia [12] and South Eastern Ethiopia [36], where patients who missed their appointments were likely to miss their doses and increase the odds of virological failure. Other studies from Myanmar [37] and Australia [38] also agreed with this finding, that missed appointments caused missed doses among patients on ART.…”
Section: Discussionsupporting
confidence: 91%
“…These variations in the virologic failure rates might be attributed to the differences in geographical areas, follow-up durations, and the types of ART regimens used.Considerably, this study reported that patients with WHO stages IV during the initiation of ART were more likely to develop virologic failure than others (OR = 12.5; CI = 2.3-67.1; P = 0.003). Consistently, Desalegn G et al (8), Mamo A et al(42) and Fiona M et al(45) stated that advanced WHO clinical stages were signi cant risk factors for virological treatment failure. The present study showed that those with poor adherence levels were three times more likely to develop virological treatment failure when compared to those with good adherence levels (OR = 23.1; CI: 3.9-136.1; P = 0.001).…”
mentioning
confidence: 67%
“…However, only 22% of the estimated PLHIV will be under treatment by the end of 2019. Planned efforts were severely affected by the political instability in the country during 2019 (40)(41)(42)(43). Moreover, regular treatment failure detection is low because of inadequate capacity and a lack of laboratory facilities in resource-limited settings, including Sudan.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that the risk of AIDS-related death in patients with clinical stage III/IV disease was higher than that in patients with stage I/II disease. HIV-infected patients with asymptomatic signs at baseline have a lower risk of death after antiretroviral therapy, suggesting that early HAART is beneficial to maintaining and rebuilding immune function, delaying disease progression, and reducing mortality [ 21 ].…”
Section: Discussionmentioning
confidence: 99%